2012
DOI: 10.1523/jneurosci.1737-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

In VivoReversible Regulation of Dendritic Patterning by Afferent Input in Bipolar Auditory Neurons

Abstract: Afferent input regulates neuronal dendritic patterning locally and globally through distinct mechanisms. To begin to understand these mechanisms, we differentially manipulate afferent input in vivo and assess effects on dendritic patterning of individual neurons in chicken nucleus laminaris (NL). Dendrites of NL neurons segregate into dorsal and ventral domains, receiving excitatory input from the ipsilateral and contralateral ears, respectively, via nucleus magnocellularis (NM). Blocking action potentials fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…High‐resolution imaging studies demonstrated intense dendritic localization of FMRP, particularly in dendritic branch points and distal endings, in NL (chicken and alligator) and MSO (gerbil and human) . In the chicken NL, the branching points are thought to be a site for initiating activity‐dependent dendritic reorganization . A proteomic study specifically targeting the chicken NL identified a number of dendritic proteins whose mRNAs are potential FMRP targets .…”
Section: Fmrp Regulates the Development Of Synaptic Transmission In Tmentioning
confidence: 99%
“…High‐resolution imaging studies demonstrated intense dendritic localization of FMRP, particularly in dendritic branch points and distal endings, in NL (chicken and alligator) and MSO (gerbil and human) . In the chicken NL, the branching points are thought to be a site for initiating activity‐dependent dendritic reorganization . A proteomic study specifically targeting the chicken NL identified a number of dendritic proteins whose mRNAs are potential FMRP targets .…”
Section: Fmrp Regulates the Development Of Synaptic Transmission In Tmentioning
confidence: 99%
“…Organelles such as ribosomes, the secretory endoplasmic reticulum, and the Golgi complex are trafficked by minus end-directed transport and are thus enriched in dendrites, where they contribute to branch initiation and differentiation. The endoplasmic reticulum exhibits zones of structural complexity in dendrites that spatially correlate with both insertion of proteins into the plasma membrane and branch formation (Cui- Wang et al 2012). The Golgi complex influences branching through discrete and mobile structures called Golgi outposts, which regulate postGolgi trafficking and facilitate microtubule nucleation at nascent branch points (Horton et al 2005, Ori-McKenney et al 2012, Ye et al 2007).…”
Section: A Dendrite Is Bornmentioning
confidence: 99%
“…In some systems, loss of neural activity is responsible for the changes. In chick auditory brainstem, removal of the cochlea or spike suppression by tetrodotoxin (TTX) causes site-specific dendrite shrinkage in the NL similar to that observed after afferent ablation (Wang & Rubel 2012). As the NL is two synapses upstream from the cochlea, these manipulations do not directly remove afferents but instead reduce their activity.…”
Section: Wwwannualreviewsorg • Mechanisms Of Dendrite Development 2mentioning
confidence: 99%
See 1 more Smart Citation
“…For example in the chick auditory brainstem, ipsilateral and contralateral afferents from the Nucleus Magnocellularis contact the dorsal and ventral arbors of the Nucleus Laminaris neurons respectively (Parks and Rubel, 1975 and Figure 4A). Accordingly, for these neurons, perturbing transmission from one set of afferents leads to connectivity changes only in their contacted dendritic arbor (Benes et al, 1977; Sorensen and Rubel, 2006; Wang and Rubel, 2012). Some activity-dependent competitive interactions occur between parallel fibers and climbing fibers that overlap marginally (Figure 4A) on the dendritic arbor of cerebellar Purkinje cells (Hashimoto et al, 2001; Ichikawa et al, 2002; Miyazaki et al, 2004; Uemura et al, 2007; Watanabe and Kano, 2011).…”
Section: Cellular and Network Design Constraints On Activity-dependenmentioning
confidence: 99%